Ответ:
Пошаговое объяснение:
[tex]10m*(-1.7)*n=10*(-1.7)*m*n=-17*m*n[/tex]
[tex]-7a*3b*(-6c)=-7*3*(-6)*a*b*c=126*a*b*c[/tex]
[tex]16x*(-\frac{8}{15}b)*\frac{45}{64} k=16*-(\frac{8}{15} )*\frac{45}{64} *b*k*x =-\frac{128}{15} *\frac{45}{64} *b*k*x=-6*b*k*x[/tex]
[tex]-\frac{5}{18} *(-\frac{4}{13} )*\frac{9}{25} *(-26)=\frac{10}{117} *\frac{9}{25} *(-26)=\frac{2}{65} *(-26)=\frac{2}{65} *-\frac{26}{1} =-\frac{4}{5} =-0.8[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Пошаговое объяснение:
[tex]10m*(-1.7)*n=10*(-1.7)*m*n=-17*m*n[/tex]
[tex]-7a*3b*(-6c)=-7*3*(-6)*a*b*c=126*a*b*c[/tex]
[tex]16x*(-\frac{8}{15}b)*\frac{45}{64} k=16*-(\frac{8}{15} )*\frac{45}{64} *b*k*x =-\frac{128}{15} *\frac{45}{64} *b*k*x=-6*b*k*x[/tex]
[tex]-\frac{5}{18} *(-\frac{4}{13} )*\frac{9}{25} *(-26)=\frac{10}{117} *\frac{9}{25} *(-26)=\frac{2}{65} *(-26)=\frac{2}{65} *-\frac{26}{1} =-\frac{4}{5} =-0.8[/tex]